Consumption pattern: A comparative study with specific reference to The Engel’s Law of two different income groups in Bangsar / Leong Yoke Kim - Leong , Yoke Kim (1986)
This academic exercise is an attempt to test the validity of the Engel’s Law in the context of consumption pattern. Attention is directed towards two different income groups with the aim of achieving its objectives through comparisons. The study has been arranged into 5 chapters, beginning with Chapter I as introduction, which discusses the objectives of the study. Other matters discussed in this chapter include the target groups chosen, the area selected and the methodology used for the study lastly the limitations of survey data. Chapter II outlines the various definitions, concepts and theories used in the study. Special attention was directed to the Engel’s Law and consumer behavior. Chapter III is a detailed analysis on the life-styles of the high income respondents with specific reference on their monthly income-expenditure relation and monthly consumption pattern. Chapter IV on the hand aims at analysing the life-styles of the low income respondents with close scrutiny on their monthly income-expenditure relation and monthly consumption pattern. Chapter V sums up the discussion with an attempt to compare and contrast the consumption pattern of the two different income groups chosen for the study. At the same time, conclusion regarding the validity of the Engel’s Law are drawn from the findings.